First-line treatment options for PD-L1-negative lung adenocarcinoma: a real-world analysis - Lijuan Chen; Lijuan Chen; Jie Liu; Jie Liu; Junfeng Lu; Junfeng Lu; Xiufeng Hu; Xiufeng Hu; Erjing An; Erjing An; Yanqiu Zhao; Yanqiu Zhao (Frontiers in Oncology)
ObjectiveTo evaluate the optimal first-line treatment options for programmed death-ligand 1 (PD-L1) negative lung adenocarcinoma (LUAD) patients without common gene-alterations.MethodsA total of 159 PD-L1-negative LUAD patients without common gene-alterations were included. Chemotherapy was administered in 44 cases (group A), immunotherapy-chemotherapy combinations in 55 cases (group B) and bevacizumab plus chemotherapy in 60 patients (group C). A head-to-head comparison of the clinical effectiveness and safety for these standard treatment regimens was conducted.ResultsThe median follow-up time was 30.9 months. For the entire cohort, median PFS was 6.67 months [95% CI 5.83-7.51], and median OS was 15.83 months [95% CI 13.46-18.21]. OS was significantly longer in group C versus others (C vs B median 21.6 months [95% CI 17.78-25.42] vs 12.63 months [95% CI 8.14-17.13]; HR 0.59 [95% CI 0.39-0.9], P = 0.01; C vs A median 21.6 months [95% CI 17.78-25.42] vs 13.47 months [95% CI 9.68-17.26], HR 0.47 [95% CI 0.3-0.71], P= 0.001), but no substantial difference was noted between group A and B (HR 0.78 [95% CI 0.51-1.2], P= 0.26). For PFS in pairwise comparison, group B and C were statistically superior to group A (B vs A median 5.6 months [95% CI 4.56-6.64] vs 5.17 months [95% CI 4.09-6.25]; hazard ratio (HR) 0.56 [95% CI 0.37-0.87], P = 0.009; C vs A median 8.57 months [95% CI 7.47-9.66] vs 5.17 months [95% CI 4.09-6.25]; HR 0.43 [95% CI 0.28-0.7], P< 0.001), whereas no significant difference was found between group B and C (HR 0.76 [95% CI 0.51-1.11], P= 0.16). The disease control rate (DCR) improvement was sustained with group C (A vs B vs C: 84.09% vs 83.64% vs 96.67%, respectively (P<0.05)). Multivariate analysis showed that the performance status score and treatment regimen were factors influencing PFS as well as OS. The treatment-emergent adverse events (AEs) of grade 3–4 occurred in a similar proportion of patients in each group (P>0.05), and all AEs were manageable without fatal toxicities.ConclusionsBevacizumab plus chemotherapy should be prioritized in PD-L1-negative LUAD patients without common driver gene alterations. These findings may facilitate individualized treatment options.